Human ecology studies and higher education for sustainable development: european experiences and examples - Franz-Balsen, Angela; Kruse-Graumann, Lenelis (oekom, 2016)
Higher Education for Sustainable Development (HESD) and Human Ecology (HE) Studies both focus on the interrelationships between people and the environment. Both approaches represent innovative academic cultures that aim at qualifying future professionals and decision-makers. Nevertheless, potential synergies between HESD and HE Studies have not yet been explored. Examples of curriculum development at European universities illustrate the barriers, the progress, and the innovative potential of HE Studies and of HESD, while the presentation of student initiatives for sustainable development in higher education testifies the political commitment of today†™s students. The objective of this compilation is to stimulate European exchange and cooperation. One of the major insights is that the joining of forces between HE Studies and HESD is overdue. Sharing the same aims, the two approaches could complement each other and provide valuable experiences for more sustainability in higher education policies - against the backdrop of the UN-Decade of Education for Sustainable Development (2005 -2014) and the post-2015 agenda.
Literaturangaben
Keywords: Aufsatzsammlung; Hochschulbildung; Nachhaltigkeit; Humanökologie